Pengaruh Nilai Kegunaan dan Keunikan Desain Terhadap Keputusan Pembelian Produk Home Decor Plaster Air Freshener - Angela Priscila Montolalu; Marina Wardaya (Jurnal Vicidi, 2019)
In recent time, the trend and the people’s interests in home decor products are growing rapidly. So now, home decor products should have more added value, so it can be more attractive to the customers.The objective of this study is to determine the value and the uniqueness about the plaster air freshener as the home decor products. There are two methods of this study such as qualitative and quantitative methods. The activities we did to do the qualitative methods are by interviewing the experts and the end-users (expert user and extreme user), and also a literature study from books and journals. However, the activities that will be done for doing quantitative methods in this study are by taking an online questioner to 50 target markets who are interested in home decors and fragrances. The result of this study indicates that the usefulness and design uniqueness of a product play important role in affecting home decor product purchase decision especially plaster air freshener.